2017
DOI: 10.1099/jgv.0.000922
|View full text |Cite
|
Sign up to set email alerts
|

Influenza virus replication in macrophages: balancing protection and pathogenesis

Abstract: Macrophages are essential for protection against influenza A virus infection, but are also implicated in the morbidity and mortality associated with severe influenza disease, particularly during infection with highly pathogenic avian influenza (HPAI) H5N1 virus. While influenza virus infection of macrophages was once thought to be abortive, it is now clear that certain virus strains can replicate productively in macrophages. This may have important consequences for the antiviral functions of macrophages, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
88
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(96 citation statements)
references
References 92 publications
1
88
0
1
Order By: Relevance
“…[276][277][278] In viral diseases, the macrophage response might be subverted to a certain extent by the numerous escape mechanisms that viral agents use to resist the host immune response. [279][280][281][282][283][284][285][286][287][288][289] Nevertheless, viruses generally trigger a response mediated by M1 macrophages that might contribute to the severity of the disease. In hepatitis C, chronic infection can lead to cell damage and cirrhosis, and the virus can induce an immune response, targeting the viral protein NS3, mediated by IL-12 and TNF-α produced by M1 macrophages.…”
Section: Autophagymentioning
confidence: 99%
“…[276][277][278] In viral diseases, the macrophage response might be subverted to a certain extent by the numerous escape mechanisms that viral agents use to resist the host immune response. [279][280][281][282][283][284][285][286][287][288][289] Nevertheless, viruses generally trigger a response mediated by M1 macrophages that might contribute to the severity of the disease. In hepatitis C, chronic infection can lead to cell damage and cirrhosis, and the virus can induce an immune response, targeting the viral protein NS3, mediated by IL-12 and TNF-α produced by M1 macrophages.…”
Section: Autophagymentioning
confidence: 99%
“…Macrophages play a critical role in the regulation and induction of innate and adaptive immune responses and protection of the host against pathogens (15,62), especially viruses (19,20,37,38,63). However, recent findings demonstrated that macrophages could be a double-edged sword in virus clearance and pathology: they not only help fight against virus infection, but may also contribute to virus production and dissemination during viral infections (26,64). In mammal models, a number of viruses have been found target macrophages and impair the function of these cells (65)(66)(67).…”
Section: Discussionmentioning
confidence: 99%
“…The M1/M2 responses from virus infection must be balanced by inhibitory and regulatory effector mechanisms to protect bystander cell, tissue and organ damage from the effects of excess inflammation, preserve oxygenation, and promote host tissue and organ repair after viral clearance (22)(23)(24)(25). As their mammalian counterpart, plasticity also is a hallmark of chicken macrophages, and in response to microenvironment signals, including microbial infection and pathogenesis of infectious diseases (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36), these cells undergo different forms of polarized activation, the extremes of which may called pro-inflammatory M1-like macrophages and anti-inflammatory M2-like macrophages.…”
mentioning
confidence: 99%
“…First, chemotactic signals important for the spatiotemporal distribution of immune cells are still largely unknown in ferrets; for example, influenza‐infected epithelial cells secrete CCL‐2 which recruits monocytes to the lungs during early infection and may be associated with acute lung injury during severe infections. Secondly, different innate immune subsets such as natural killer (NK) cells, dendritic cells (DCs), monocyte/macrophages and granulocytes have also yet to be studied in detail, and development of reagents to allow the delineation of these cell populations (reviewed in) will enable a more detailed picture of early immune responses in ferrets. Thirdly, while adaptive immune responses have been studied in ferrets, markers to delineate B/T‐cell subpopulations will be useful to study long‐term protection against influenza infection (as reviewed in).…”
Section: Ferrets As An Immunological Model For Studying Influenzamentioning
confidence: 99%